Analysis and characterization of X-ray events in medium voltage vacuum interrupters under Lightning Impulse Voltage - Marconato, Nicolo; Pilan, Nicola; Gobbo, Renato; Bettini, Paolo; Lorenzi, Antonio De; Lawall, Andreas; Taylor, Erik D.; Pino, Felix (Proceedings - International Symposium on Discharges and Electrical Insulation in Vacuum, 2023)
The experience gained in the study of conditioning of high voltage vacuum-isolated DC systems with X-ray detectors, which allows analysis of time windows with a resolution of a few tens of ns, suggested to explore the use of this technique for studying the voltage holding of Vacuum Interrupters. The analysis of X-ray events to investigates the mechanisms causing breakdowns and electrode conditioning process under Lightning Impulse Voltage Waveform is the subject of the present contribution, with the aim of improving the knowledge to predict the breakdown probability of medium voltage Vacuum Interrupters. An ad hoc experimental campaign on Siemens VI models have been carried out at the high voltage laboratory of the Industrial Engineering Department of the Padua University, with two X-rays detectors based on LYSO inorganic scintillator, which have never been applied in this context.The paper describes the measurement setup, which has been carefully implemented in order to be immune to the electromagnetic noise due to the fast LIV discharge, and the analyses of data from this preliminary experimental campaign.